Features of colour autoidentification and self-estimation for patients with paranoid schizophrenia at research of adherence to psychopharmacotherapy - Korzh, Anastasia (Psychiatry, Neurology and Medical Psychology, 2018)
In work data are provided on studying self-identification on the basis of the color test of the relations at patients with paranoid schizophrenia at various degrees of adherence to treatment. The analysis of associations of colors with emotionally significant persons and concepts has shown that in general the patients with the low level of adherence to treatment neuroleptics / anti-psychotics have established the most pessimistic associations connected with negative values of colors in relation to health and a disease. In the specified group, in comparison with patients with moderate and satisfactory degree of adherence to therapy, low indicators of the relation of patients to treatment are found that is established when using a methodic of a self-estimation, also indicators of health, understanding a disease, trust to the doctor and advantage of treatment. In the group with a moderate degree of adherence to treatment, that is, with partial compliance, the examined patients considered themselves healthier, determined a satisfactory character, realized the benefits of treatment, which was correlated with similar clinical and psychopathological data. The level of self-esteem in patients with a satisfactory attitude to treatment was significantly higher in all indicators. Based on the results of the self-assessment study, correlates of adherence to treatment of varying degrees were established.